Glucosinolates, a natural chemical arsenal: More to tell than the myrosinase story - Abdel-Massih, Roula M.; Debs, Espérance; Othman, Leen; Attieh, Jihad; Cabrerizo, Franco M. (Frontiers in Microbiology, 2023)
Glucosinolates are a group of thioglucosides that belong to the class of plant nitrogen-containing natural products. So far, very little biological activity has been associated with intact glucosinolates. The hydrolysis of glucosinolates has, for long, attracted attention because of the potent biological activity of the hydrolysis products. From allelopathic to antiparasitic, antimicrobial and antineoplastic effects, the activity spectrum of the degradation products of typical glucosinolates has been the subject of much research. The present review seeks to address the various means of glucosinolate degradation (thermal, enzymatic, or chemical degradation) and the ensuing products. It also aims to draw a comparative profile of the various antimicrobial effects of these degradation products to provide a further understanding of the biological function of these important compounds.